EVALUATING INTERNATIONAL MONETARY POLICIES ON THE STABILITY OF FINANCIAL MARKETS IN IRAQ - Lecturer Mustafa Ismail Khalil; Esraa Saad Fahad (Scholars Digest Publishing, 2023)
Through research, the relationship between international monetary policy indicators and the financial stability of the Iraqi stock market has been clarified. A comprehensive indicator reflecting the financial stability of the Iraqi stock market was used to provide appropriate suggestions for policymakers to address the financial stability issue in the Iraqi stock market. The study also focused on the current analysis of crises in financial markets and provided solutions to avoid future crises. From here, the research question arises regarding the impact of international monetary policy on the stability of global financial markets, including the Iraqi stock market. The period from 2000 to 2022 was chosen based on annual data, and the relationship between international monetary policy indicators and financial market stability was studied. The study supports the hypothesis that monetary policy affects financial market stability through the financial market stability indicator. It has been found that lending policies increase the financial market stability indicator. Suppose the national treasury succeeds in proposing the establishment of a sovereign fund to play a supportive role in helping the Iraqi stock market overcome the crisis. In that case, the Central Bank of Iraq needs to adopt this indicator to deal with the negative impact of international monetary policy on the Iraqi economy.
Keywords: international monetary policies, aggregate index, financial markets.